Closest friendships of black college students: Social intimacy - Peretti, Peter O. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Literature focuses on the formation of friendship, largely in terms of similarities of attitudes and experiences. Some of it suggests the significance of social intimacy in the friendship structure and its influences on personality and social consequences. Using ego’s perception of his closest friendship unit, the present study attempted to study social intimacy of closest friendships of black college students, and social intimacy based on structural characteristics of the group formed by members of the same and of the opposite sex. Results found different degrees in the range of social intimacy between closest friendships of same and opposite sex members. Among the structural networks of both heterosocial and homosocial friendships, dyadic forms of relations tended to be the most socially intimate.